2009
DOI: 10.1007/s10750-008-9692-6
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate cycles of decline and recovery in Swan Coastal Plain (Western Australia) wetlands affected by drought-induced acidification

Abstract: Management of wetlands influenced by the Gnangara groundwater mound, Western Australia, is becoming increasingly challenging due to an ongoing decline in the regional groundwater table. A number of these groundwater-dependent wetlands have acidified (with adverse effects on the extant macroinvertebrate fauna) due to the oxidation of pyritic sediments. One management option in such cases is artificial augmentation of surface water in order to maintain or reinstate anaerobia in the sediments. This paper document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…This result, showing the isopod C. carinata as the species with the highest differences between pH treatments, is according Sommer and Horwitz (2009) who identified the isopod (as taxonomic group) as one of most acid-sensitive aquatic macroinvertebrates. These authors argued that this is due to respiratory and ion-regulatory failure, and probably to possessing a calcified exoskeleton, as well.…”
Section: Groupssupporting
confidence: 64%
See 1 more Smart Citation
“…This result, showing the isopod C. carinata as the species with the highest differences between pH treatments, is according Sommer and Horwitz (2009) who identified the isopod (as taxonomic group) as one of most acid-sensitive aquatic macroinvertebrates. These authors argued that this is due to respiratory and ion-regulatory failure, and probably to possessing a calcified exoskeleton, as well.…”
Section: Groupssupporting
confidence: 64%
“…However, despite no literature was found about the amphipod J. marmorata, Haunton et al (2009) reported no significant difference in the percent of mortality in the amphipod Gammarus locusta exposed to different pH levels (from 8.1 to 7.6), defending the hypothesis that this is a robust species. Therefore, our results are according to Sommer andHorwitz (2009), Wood et al (2014), Ferreira et al (2004) and Haunton et al (2009).…”
Section: Groupsmentioning
confidence: 56%
“…Many studies have reported that such taxa are sensitive to changes in water quality, particularly those induced by drought and dry conditions (Heino 2005, Bowman et al 2006, Miller et al 2009, Sommer and Horwitz 2009. Tolerant families in edges generally respire through their teguments, and a greater prevalence of taxa with tegument respiration typifies areas with modified flow regimes and other human perturbations (Charvet et al 2000, Tomanova et al 2008.…”
Section: ]mentioning
confidence: 99%
“…The lowered groundwater levels have also contributed to the acidification of several wetlands in the area through the exposure of acid sulphate soils. Artificial maintenance of water levels has been shown to restore some of the impact of droughtinduced acidification on macroinvertebrate communities but change the seasonal hydrological regime of the wetlands (Sommer and Horwitz 2009).…”
Section: Crau Aquifer: a Water Circular Economymentioning
confidence: 99%